Effectiveness of Size, Liquidity, Leverage, and Growth on CSR Disclosure Moderating Role by Profitability in Indonesian Stock Exchange (IDX) - Dwi Fatmah Sari; Eko Hariyanto; Sri Wahyuni; Novi Dirgantari (Universitas Medan Area, 2023)
The conduct of this study emphasizes the purpose of determining the presence or absence of the influence of profitability which acts as moderating in the influence of company size, liquidity, leverage, and company growth on CSR disclosure. This research focuses on sectors that have been classified as consumer non-cyclicals listed on the Indonesia Stock Exchange (IDX) during 2018-2021. The theory carried in this study refers to the theory of legitimacy and stakeholders. With regard to the theory of legitimacy, it is clearly affirmed that organizations always seek to be perceived as operating within the limits and norms of the prevailing society and put more emphasis on public rights. Meanwhile, in stakeholder theory, it is said that a company must be an organization whose actions can contribute to its stakeholders. Therefore, the support provided by stakeholders affects the existence of the company itself and this support plays an important role in maintaining the company's life. The procedure in the sampling process is by purposive sampling and obtained by 28 companies. The data analysis model applied in this study includes descriptive statistics, multiple linear regression analysis, and residual test MRA and by utilizing SPSS 26 software. The results of this study prove that CSR disclosure cannot be influenced by company size or company growth. Meanwhile, CSR disclosure can be affected by liquidity and leverage. The results of moderated regression analysis through residual testing have proven that the relationship between company size, liquidity, leverage, and company growth with CSR disclosure cannot be strengthened by profitability.